Suppression of Conditional TDP-43 Transgene Expression Differentially Affects Early Cognitive and Social Phenotypes in TDP-43 Mice - Silva, Pablo R.; Nieva, Gabriela V.; Igaz, Lionel M. (Frontiers in Genetics, 2019)
Dysregulation of TAR DNA-binding protein 43 (TDP-43) is a hallmark feature of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), two fatal neurodegenerative diseases. TDP-43 is a ubiquitously expressed RNA-binding protein with many physiological functions, playing a role in multiple aspects of RNA metabolism. We developed transgenic mice conditionally overexpressing human wild-type TDP-43 protein (hTDP-43-WT) in forebrain neurons, a model that recapitulates several key features of FTD. After post-weaning transgene (TG) induction during 1 month, these mice display an early behavioral phenotype, including impaired cognitive and social function with no substantial motor abnormalities. In order to expand the analysis of this model, we took advantage of the temporal and regional control of TG expression possible in these mice. We behaviorally evaluated mice at two different times: after 2 weeks of post-weaning TG induction (0.5 month group) and after subsequent TG suppression for 2 weeks following that time point [1 month (sup) group]. We found no cognitive abnormalities after 0.5 month of hTDP-43 expression, evaluated with a spatial working memory task (Y-maze test). Suppression of TG expression with doxycycline (Dox) at this time point prevented the development of cognitive deficits previously observed at 1 month post-induction, as revealed by the performance of the 1 month (sup) group. On the other hand, sociability deficits (assessed through the social interaction test) appeared very rapidly after Dox removal (0.5 month) and TG suppression was not sufficient to reverse this phenotype, indicating differential vulnerability to hTDP-43 expression and suppression. Animals evaluated at the early time point (0.5 month) post-induction do not display a motor phenotype, in agreement with the results obtained after 1 month of TG expression. Moreover, all motor tests (open field, accelerated rotarod, limb clasping, hanging wire grip) showed identical responses in both control and bigenic animals in the suppressed group, demonstrating that this protocol and treatment do not cause non-specific effects in motor behavior, which could potentially mask the phenotypes in other domains. Our results show that TDP-43-WT mice have a phenotype that qualifies them as a useful model of FTD and provide valuable information for susceptibility windows in therapeutic strategies for TDP-43 proteinopathies.